2001
DOI: 10.1046/j.1468-3083.2001.00268.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of elastic skin fibres from patients with: cutis laxa, anetoderma, pseudoxanthoma elasticum, and Buschke-Ollendorff and Williams-Beuren syndromes

Abstract: Computed morphometric analysis of elastic skin fibres in patients with cutis laxa, anetoderma, Williams-Beuren syndrome, pseudoxanthoma elasticum (PXE), and Buschke-Ollendorff syndrome, all clinically ascertained, was performed and compared with data obtained from healthy individuals of the same age. The diameters, area fractions (AA%) and volume fractions (VV%) occupied by pre-elastic fibres and dermal elastic fibres were determined. Irrespective of age the diameter of dermal elastic fibres followed a Gaussia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Presumably these mild skin changes can be attributed to the ultrastructural changes in elastin. Abnormal elastin fibers with reduced amounts of amorphous elastin and decreased elastic fiber volume and diameter have been demonstrated on microscopic analysis of skin in persons with WS [Urban et al, 2000;Ghomrasseni et al, 2001]. We found that the majority of adults had premature graying of the hair starting as early as 16 years old, a finding which has been reported previously [Morris et al, 1988].…”
Section: Discussion Of Integument Findingssupporting
confidence: 78%
“…Presumably these mild skin changes can be attributed to the ultrastructural changes in elastin. Abnormal elastin fibers with reduced amounts of amorphous elastin and decreased elastic fiber volume and diameter have been demonstrated on microscopic analysis of skin in persons with WS [Urban et al, 2000;Ghomrasseni et al, 2001]. We found that the majority of adults had premature graying of the hair starting as early as 16 years old, a finding which has been reported previously [Morris et al, 1988].…”
Section: Discussion Of Integument Findingssupporting
confidence: 78%
“…28 Additional information can be gained through fluorescence lifetime imaging microscopy, whereby different cellular structures with similar emission spectra but different fluorescence decay rates can be distinguished, thus providing a reflection of the molecular environment of the fluorescent molecule, e.g. 29,30 Here, we propose an alternative measure whereby quantification of elastin provides additional information about the morphology and the absolute content of elastin in the skin. 15 Although histological studies have measured the relative content of elastin in rare elastin disorders, as well as in photoaged and chronologically aged skin, no study has attempted to quantify with MPM the absolute elastin content in the setting of solar elastosis.…”
Section: Multiphoton Microscopy Permits Imaging Of the Dermis Throughmentioning
confidence: 99%
“…In addition, there is no fragmentation of the fibers. Computed morphometric analysis showed that volume fractions of dermal elastic fibers were four- to fivefold increased in Buschke-Ollendorff syndrome [9]. The absence of any radiologic bone abnormalities in our patients and the histologic evidence of decreased and altered elastic fibers in the skin lesions together with a negative family history in all patients make the diagnosis of Buschke-Ollendorff syndrome unlikely.…”
Section: Discussionmentioning
confidence: 79%